Von NEBIS zu SLSP: Wie die Datenmigration des grössten Schweizer Verbundes umgesetzt wurde - Wittwer, Barbara (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2021)
On 7 December 2020, a new era for the swiss scientific libraries began with swisscovery. The six large library networks merged into one single platform, the Swiss Library Service Platform (SLSP). This was accompanied by the introduction of a new library system, Ex Libris Alma, which replaced Aleph and SFX. For the NEBIS network, formerly the largest library network in Switzerland, this meant organizing the data migration and supporting the NEBIS libraries in the change to SLSP. A change of the library management system is always associated with various challenges and unknowns. The conceptual considerations that the managers of the NEBIS system made with regard to data migration and how the countless data clean-ups were prioritized are shown below, along with the lessons learned.